Gay News : Europe's largest circulation newspaper for gays of all sexes. (London : Gay News Ltd., 1972)
Fonds Suzan Daniel (FSD)
Ondertitel varieert
Periodiciteit : tweewekelijks
Redactie : 34d. Redcliffe Square, London SW 10 : vanaf (1973) 34 : 62 A Chiswick High Road, London W4 ; vanaf (1975) 77 : 1A Normand Garden Geyhound Road, London W14 95 B ; vanaf (1982) 253 : 5th Floor, 113/117 Farringdon Road, London
Engels
Periodiek